Proteomics Revealed That Mitochondrial Function Contributed to the Protective Effect of Herba Siegesbeckiae Against Cardiac Ischemia/Reperfusion Injury - Wei, Xiaohong; Wu, Yuzhuo; Pan, Haie; Zhang, Qian; He, Ke; Xia, Guiyang; Xia, Huan; Lin, Sheng; Shang, Hong-Cai (Frontiers in Cardiovascular Medicine, 2022)
Background: Myocardial ischemia/reperfusion (I/R) injury is the main obstacle to percutaneous coronary intervention, lacking effective therapeutic measures in clinic. Herba siegesbeckiae (HS) is a traditional herb with multiple pharmacological activities, and evidence of cardiovascular protection. However, few data are available regarding the role of HS in cardiac I/R. This study aimed to explore the effect and underlying mechanism of HS aqueous extract on cardiac I/R injury. Methods: HS aqueous extract was prepared and analyzed by UHPLC-MS/MS. After intragastric administration of HS once daily for 7 days, male Sprague-Dawley rats were subjected to 30 min occlusion of left anterior descending coronary artery followed by 120 min reperfusion to elicit I/R. Myocardial infarction and apoptosis, 12-lead ECG and hemodynamics, cardiac morphology and myocardial enzymes, quantitative proteomics, mitochondrial ultrastructure and electron transport chain (ETC) function, oxidative stress and antioxidation, NLRP3 inflammasome and inflammation were evaluated. Results: The chemical constituents of HS aqueous extract were mainly divided into flavonoids, diterpenoids and organic acids. In vivo, HS aqueous extract notably alleviated myocardial I/R injury, as evidenced by reduction of infarct size, apoptotic cells and cardiac lesion enzymes, decline of ST-segment elevation, improvement of cardiac function, and preservation of morphology. Quantitative proteomics demonstrated HS reversed the alteration of Adgb, Cbr1, Decr1, Eif5, Uchl5, Lmo7, Bdh1, Ckmt2, COX7A and RT1-CE1 expression after I/R. In addition, HS preserved myocardial ultrastructure, and restored mitochondrial ETC Complexes function exposure to I/R; HS significantly suppressed I/R-elicited increase of ROS, RNS, MDA and 8-OHdG, restrained the acetylation of MnSOD, and recovered the activity of MnSOD; HS reversed I/R-induced elevation of NLRP3 inflammasome, and inhibited inflammatory factors release and pyroptosis. Conclusions: HS aqueous extract ameliorated cardiac I/R injury, which is associated with mitigating oxidative stress, suppressing NLRP3 inflammasome and restoring mitochondrial function by regulating the expression of Adgb, Cbr1, Decr1, Eif5, Uchl5, Lmo7, Bdh1, Ckmt2, COX7A and RT1-CE1.